2019
DOI: 10.3390/ani9080498
|View full text |Cite
|
Sign up to set email alerts
|

Rumen and Fecal Microbial Community Structure of Holstein and Jersey Dairy Cows as Affected by Breed, Diet, and Residual Feed Intake

Abstract: Identifying factors that influence the composition of the microbial population in the digestive system of dairy cattle will be key in regulating these populations to reduce greenhouse gas emissions. In this study, we analyzed rumen and fecal samples from five high residual feed intake (RFI) Holstein cows, five low RFI Holstein cows, five high RFI Jersey cows and five low RFI Jersey cows, fed either a high-concentrate diet (expected to reduce methane emission) or a high-forage diet. Bacterial communities from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 43 publications
4
45
0
Order By: Relevance
“…On bacterial family level, 71% changed in relative abundances with HC feeding. The highest abundant families found, do overlap with other studies investigating fecal microbiota in cattle [ 35 ] and sheep [ 36 ]. However, some studies, as [ 9 ], found almost 42% Peptostreptococcaceae in the rectum of cattle, followed by Turicibacter , and Clostridium , and [ 29 ] mainly Planococaceae , Enterobacteriaceae , Moraxellaceae , Peptostreptococcaceae , and Erysipelotrichaceae , which were all below 1% abundance or not present in our study.…”
Section: Discussionsupporting
confidence: 80%
“…On bacterial family level, 71% changed in relative abundances with HC feeding. The highest abundant families found, do overlap with other studies investigating fecal microbiota in cattle [ 35 ] and sheep [ 36 ]. However, some studies, as [ 9 ], found almost 42% Peptostreptococcaceae in the rectum of cattle, followed by Turicibacter , and Clostridium , and [ 29 ] mainly Planococaceae , Enterobacteriaceae , Moraxellaceae , Peptostreptococcaceae , and Erysipelotrichaceae , which were all below 1% abundance or not present in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatives, such as the use of oral samples as a proxy for the rumen microbiome, have been proposed [10] and shown to be good predictors for the bacteria community, but not for archaea. Other sampling alternatives for monitoring the GIT microbiome, such as colon/fecal are poorly investigated or limited to a small number of animals [11], despite being identified as crucial in other mammals [12][13][14].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…3D, E). These indicate that microbiota structures closely related to the breeding environment, feeding method, and management measures (Crippen et al, 2019;Li et al, 2019;Noel et al, 2019). There were 626 (PC) and 649 (GC) OTUs shared among PC and GC groups, representing 26.6% and 24.4% of total reads separately in PC and GC environments, respectively.…”
Section: Analysis Of Microbiota Structurementioning
confidence: 81%